Consistência das informações arquivísticas referentes ao registro e às alterações de projetos no SIE patrimônio documental da UFSM - Viana, Gilberto Fladimar Rodrigues (2011)
The objective of this work is to analyze the present situation of the registers and alterations in the file information concern to projects from Arts and Letters Center CAL, of the Federal University of Santa Maria UFSM, which compose the databases of the institution. So that, file information related to projects, collected through the access to documents and written reports from the databases of UFSM were used. Also, a questionnaire, addressed to teachers from CAL, was applied. Based on the analysis of the surveys, written reports and the questionnaire some conclusions were reached. Through the description of the system of the register of the projects it was observed that the screen participants offer much information about this participation, reflecting in the academic life of teachers and students. Another result refers to the increase evolution in the number of projects registered since the beginning of the system working. In addition, it was verified, by applying the questionnaire to teachers, many situations like those related to titles and the implications involved in the register of the projects. The analysis of the declarations collected through interviews addressed to responsible people for SIE in the CPD and PROPLAN contribute to the diagnosis of the system, mainly focusing on the authenticity and reliability of the file information available. These evidences allow presenting, in the end of the work, some recommendations to SIE improvement. So, it will hope that the results obtained in this research can be considered referential as the UFSM as other institutions that have interest in this work.